On arranging the procedure of public debate on the educational curriculum draft for Master students majoring in 014 Secondary Education (Mathematics), academic discipline 01 Education/Pedagogics - Kateryna Vlasenko; Olha Rovenska; Iryna Lovianova; Svetlana Korchagina; Helen Zahrebelna; Iryna Dmytryshyn (Освітній вимір, 2020)
The present study describes the efficient arrangement of the process of debating on the educational curriculum draft for “Secondary education (Mathematics)” for Master students of an academic discipline 01 “Education/Pedagogics”. The article analyses the requirement of the existing regulatory documents by the National Agency for Higher Education Quality Assurance and methodological recommendations by leading universities on developing educational curricula. The analysis of the survey resources in demand allowed the authors of this paper to identify an on-line constructor of questionnaires through the Google Forms on-line constructor of questionnaires. The study presents the context and content of the questions of a Google form “Debate on the educational curriculum draft for Secondary school (Mathematics)”. The researchers defined the stages for arranging the procedure of the public debate on the draft. Surveying the stakeholders was done through personal messages, placing links to the official web-page of the Mathematics department and modelling on Facebook, Telegram and e-mails. The analysis of the stakeholders' answers facilitated designing the recommendations for enhancing the educational curriculum and establishing cooperation in the educational process.